Prophylactic Antibiotics in the Prevention of Infection After Operative Vaginal Delivery (ANODE): A Multicenter Randomized Controlled Trial. Issue 1 (March 2020) - Knight, M.; Chiocchia, V.; Partlett, C.; Rivero-Arias, O.; Hua, X.; Hinshaw, K.; Tuffnell, D.; Linsell, L.; Juszczak, E.
Abstract : ( Lancet . 2019;393:2395–2403) Sepsis is responsible for 11% of maternal deaths worldwide, and it is not limited to low- and middle-income countries. Even in high-income countries, sepsis accounts for ∼5% of maternal deaths; in the United States, the rate might be as high as 13%. Risk factors for sepsis have been identified and include cesarean and operative vaginal (use of forceps or vacuum extraction) deliveries. Several studies have reported a 60% to 70% decrease in postoperative infections after cesarean delivery with the administration of prophylactic antibiotics. However, due to a lack of evidence, routine antibiotic prophylaxis is not recommended for operative vaginal deliveries. The aim of this randomized, controlled multicenter study was to determine whether antibiotic prophylaxis prevented maternal infection after operative vaginal birth.